Diagnostic laparoscopy should be performed before definitive resection for pancreatic cancer: a financial argument. Issue 2 (February 2015) - Jayakrishnan, Thejus T.; Nadeem, Hasan; Groeschl, Ryan T.; George, Ben; Thomas, James P.; Ritch, Paul S.; Christians, Kathleen K.; Tsai, Susan; Evans, Douglas B.; Pappas, Sam G.; Gamblin, T. Clark; Turaga, Kiran K.
Abstract: Objectives: Laparoscopy is recommended to detect radiographically occult metastases in patients with pancreatic cancer before curative resection. This study was conducted to test the hypothesis that diagnostic laparoscopy (DL) is cost‐effective in patients undergoing curative resection with or without neoadjuvant therapy (NAT). Methods: Decision tree modelling compared routine DL with exploratory laparotomy (ExLap) at the time of curative resection in resectable cancer treated with surgery first, (SF) and borderline resectable cancer treated with NAT. Costs (US) from the payer's perspective, quality‐adjusted life months (QALMs) and incremental cost‐effectiveness ratios (ICERs) were calculated. Base case estimates and multi‐way sensitivity analyses were performed. Willingness to pay (WtP) was US4166/QALM (or US50 000/quality‐adjusted life year). Results: Base case costs were US34 921 for ExLap and US33 442 for DL in SF patients, and US39 633 for ExLap and US39 713 for DL in NAT patients. Routine DL is the dominant (preferred) strategy in both treatment types: it allows for cost reductions of US10 695/QALM in SF and US4158/QALM in NAT patients. Conclusions: The present analysis supports the cost‐effectiveness of routine DL before curative resection in pancreatic cancer patients treated with either SF or NAT.